Com grandes poderes, vêm grandes responsabilidades: um estudo etnometodológico sobre o leitor e a leitura de histórias em quadrinhos de super-heróis da Marvel e da DC Comics - Rubem Borges Teixeira Ramos (2017)
Analises, presents and discusses brazilian and US readers experiences regarding Marvel and DC superhero comics. Through comics reading, the reader is exposed to naenourmous variety of ideas and values, which led to a continuous knowledge restructuring and internalization. This reading is considered both as a source and format for information ownership and knowledge introjection. It aims to contemplate and to interpret these comics conceptions by both audiences, brazilian and American, as well as to identify their contexts, meanings and motivations in order to implement and proceed with this particular reading, even as they enter the adult life. For this purpose, it appeals to articulate among scholars and theories which provide state to proceed further investigations in terms of the superhero comic book reader and his knowledge introjection, acquired by means of this reading, as Garfinkels etnomethodology (1963), which allows to contemplate the readers common sense and meaning and importance references; Geertz (1978) with the cultural studies which allows the access to elements that affect the reader inside his social context; Schechners (1998) performance studies, which defines performances interpretation, applied to the act of reading not only having entertainment value, but also effectiveness, therefore capable to generate meaningful repercussions to one or several individuals before a reading and its interpretations; Isers (1996-1999) aesthetic response, which emphasizes the readers relevance as an individual aware of readings value and meaning, thanks to his capacity on rework this reading through thinking alongside his reality, and Dumont (1998), who supports the readers remake reading, which is his ability to apply one or more contents gathered through reading, such as the comics, in one or more aspects of his life. The use of participant information and interview, as well as the topic life history, in order to subsidize the methodological procedures on qualitative research. Highlights Information Sciences need to value studies oriented to understand the reader, especially the ones which allows the comprehension linked with the ability of content interpretation in a text or story taking place when this reader suggests feelings, facts and events depicted in reading, which can be introjected by the reader by means of interpretation and thinking, mainly regarding events that take place in his own life